Spillage-Adaptive Fixed-Geometry Bump Inlet of Wide Speed Range - Zonghan Yu (MDPI AG, 2021)
In this work, a new spillage-adaptive bump inlet concept is proposed to widen the speed range for hypersonic air-breathing flight vehicles. Various approaches to improve the inlet start-ability are summarized and compared, among which the bump-inlet pattern holds the merits of high lift-to-drag ratio, boundary layer diversion, and flexible integration ability. The proposed spillage-adaptive concept ensures the inlet starting performance by spilling extra mass flow away at low speed number conditions. The inlet presetting position is determined by synthetically evaluating the flow uniformity and the low-kinetic-energy fluid proportion. The numerical results show that the flow spillage of the inlet increases with the inflow speed decrease, which makes the inlet easier to start at low speed conditions (M 2.5–6.0). The effects of the boundary layer on spillage are also studied in this work. The new integration pattern releases the flow spillage potentials of three-dimensional inward-turning inlets by reasonably arranging the inlet compression on the bump surface. Future work will focus on the spillage-controllable design method.